ZIF-8과 탄소기반물질 복합체를 이용한 슈퍼커패시터 및 화학센서의 최신연구동향 - 김상준(Sang Jun Kim); 이재민(Jae Min Lee); 조승근(Seung Geun Jo); 이은빈(Eun Been Lee); 이승기(Seoung-Ki Lee); 이정우(Jung Woo Lee) (Biuletyn Uniejowski, 2022)
Metal-organic framework (MOF) is one of the representative porous materials composed of metal ions and organic linkers. In spite of many advantages of the MOFs such as high specific surface area and ease of structure control, drawbacks have become obstacles to the practical use of them with poor electrical conductivity and chemical stability. The ZIF-8, which is consisted of zinc and imidazole linker, is one of the solutions to improve the chemical stability issue. In addition, composites using the ZIF-8 and carbonbased materials are widely used to enhance the electrical conductivity. In this regard, supercapacitor is very attractive field for using the composites, because most of carbon-based materials are porous and conductive. Also, for sensor applications, the ZIF-8 composite is suitable material to meet the requirement in terms of the selectivity and sensitivity. This review summarizes recent progress of the composite materials with the ZIF-8 and the carbon-based materials for the supercapacitors and the chemical sensors. In particular, the composites are classified into ZIF-8-graphene, ZIF-8-carbon nanotube and ZIF-8-other carbon-based material.